2014
DOI: 10.1038/hr.2014.76
|View full text |Cite
|
Sign up to set email alerts
|

Six random specimens of daytime casual urine on different days are sufficient to estimate daily sodium/potassium ratio in comparison to 7-day 24-h urine collections

Abstract: The objective of this study was to determine the optimal number and type of casual (spot) urine specimens required to estimate an individual's urinary sodium/potassium (Na/K) ratio. A total of 48 participants, 25 men and 23 women, aged between 25 and 59 years, was recruited from healthy volunteers. The Na/K ratio in each casual urine and 7-day 24-h urine sample was measured. Correlation analysis and the quality of agreement by the Bland and Altman method between casual urine and 24-h urine were analyzed. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 19 publications
5
56
0
Order By: Relevance
“…3135 Since this is the first trial on the effects of self-management on urinary Na/K ratio using a self-monitoring device, we were unable to reference the findings of previous intervention studies. Thus, we referred to findings from observational studies and assumed that the intervention effect would induce a level close to the average value of either worldwide populations (urinary Na/K ratio of 3.3) or Western populations (urinary Na/K ratio of 2.2), which had lower Na/K ratios than we initially expected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3135 Since this is the first trial on the effects of self-management on urinary Na/K ratio using a self-monitoring device, we were unable to reference the findings of previous intervention studies. Thus, we referred to findings from observational studies and assumed that the intervention effect would induce a level close to the average value of either worldwide populations (urinary Na/K ratio of 3.3) or Western populations (urinary Na/K ratio of 2.2), which had lower Na/K ratios than we initially expected.…”
Section: Methodsmentioning
confidence: 99%
“…5 , 22 , 3135 A recent report from the TOHP follow-up study has reported a lower level of cardiovascular risk with urinary Na/K ratio less than 2.00. 16 We advised all participants to target a urinary Na/K ratio of less than 1.00, since WHO has suggested that achieving recommended levels of both Na and K would deliver a Na/K ratio of approximately 1.00.…”
Section: Methodsmentioning
confidence: 99%
“…As is the case for single spot urine collections, multiple spot urine collections underestimate 24‐hour urine sodium at lower 24‐hour urine sodium and overestimate at higher 24‐hour urine sodium and differences between the methods can be as much 7000 mg sodium . Current data do not support using single or multiple spot or short‐term timed urine collections to assess individual sodium intake …”
Section: Use Of Spot and Short Duration Timed Urine Collections To Asmentioning
confidence: 95%
“…47 Current data do not support using single or multiple spot or short-term timed urine collections to assess individual sodium intake. 47,54,55…”
Section: Us E Of S P Ot and S Hort Dur Ati On Timed Urine Collec Timentioning
confidence: 99%
“…However, these studies used 24-h urine samples, and availability of Na/K data for spot urine samples is limited, despite a strong correlation being observed between spot urine Na/K and BP levels [14]. Recently, Iwahori et al [15] reported that mean value of repeated measurement of spot urine Na/K was closely correlated to 24-h urine sample Na/K. These previous data emphasize the importance of elucidating the association of spot urine Na/K with BP levels and target organ damage, as well as clinical and environmental factors that might affect Na/K.…”
mentioning
confidence: 98%